PRODUCTION PERFORMANCE OF KAMPUNG CHICKEN FILLED FEEDING CONTAINING CHICORY FLOUR - Deki Zulkarnain; Achmad Selamet Aku; La Ode M Munadi (Jambura Journal of Animal Science, 2023)
Balitnak Superior Kampong Chicken is a type of kampong chicken resulting from research innovation from the Livestock Research Institute, Ciawi, Bogor which is popular with the community and can be cultivated by the community. This study aimed to analyze the performance of balitnak superior kampong chickens given chicory flour and to find out the best treatment for the addition of chicory flour in feeding the performance of balitnak superior kampong chickens. The design used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications so that there were 20 experimental units and each replication consisted of 5 chickens. The parameters observed consisted of feed consumption, body weight gain, and feed conversion. The results of observations from the addition of chicory flour did not have a significant effect (P0.05) on feed consumption, body weight gain, and feed conversion with a ration consumption value of 58,47-59,46 g/head/day, the average weight gain body 17,70-18,62 g/head/day, and feed conversion 3,20–3,36